KAJIAN KUALITAS AIR SUNGAI DENGKENG DI KECAMATAN BAYAT, KABUPATEN KLATEN, JAWA TENGAH - Wawan Budianta; Sutrisno (KURVATEK, 2021)
Dengkeng River was one of the tributary rivers of Bengawan Solo river that flow in Kebon Village, Bayat Sub-district, Klaten District, Central Java Province. In the area of Bayat Sub-district, there are several batik industries near the Dengkeng River. This industry generated wastewater which influenced Dengkeng River water quality in the study area. This study aimed to investigate and analyze the water quality of the Dengkeng River in the study area. Ten river water samples were obtained in the long river water stream from upstream to downstream. The sampling was conducted in August 2021, and the river water sampling was sampled referred to the SNI procedure. Several water quality parameters were measured, including pH, TDS, EC, BOD, COD, and phenol. The water pollution index and river pollution loading was calculated to analyze the river pollution level. The result of the study shows that all parameter measured was below the threshold of water quality standard for class I, II, III and IV, except for COD parameter, which exceeds the threshold for water quality standard class I. Generally, the water quality in the river in the study area shows that the level of pollution was increased from upstream to downstream due to the presence of batik wastewater generated in the middle of the river stream up to downstream. The presence of batik wastewater has a significant contribution to the increasing water quality parameter level. The pollution index calculation results show that the status of river water quality standard in the study area includes the good category in the upstream, however in the middle to the downstream including for low polluted level category. The pollution load index calculation shows that generally, the pollution loading increase from upstream to downstream due to the batik wastewater. The study recommends better river water quality monitoring, maintenance of wastewater treatment facility and community participation for river management.